Digital Transformation of Waqf Institutions and Its Impact on Financial Sustainability - Anila Dani Sakinah (Study Program of Sharia Business Management , Faculty of Islamic Economics and Business, 2025)
This study examines how digital transformation shapes the financial sustainability of waqf institutions, focusing on the adoption of digital platforms, data management systems, and technology-enabled governance mechanisms. Using a qualitative multiple-case approach supported by institutional reports and interviews, the research explores how digital tools influence fundraising efficiency, transparency, asset management, and long-term financial stability. The findings indicate that digitalization enhances the accuracy of beneficiary databases, accelerates administrative processing, and strengthens accountability through real-time monitoring and traceable transactions. Moreover, technology-based fundraising channels expand donor reach and increase cash-waqf collection, while digital asset management systems improve the utilization and productivity of waqf properties. However, the study also identifies challenges related to digital literacy, cybersecurity risks, and uneven technological readiness among institutions. Overall, the results demonstrate that digital transformation serves as a critical enabler of financial sustainability, provided that waqf institutions align technological adoption with governance reforms and strategic resource management.